О происхождении столбовых гробниц Лесостепи скифского времени - Гречко, Д.С. (My University, 2013)
Стаття присвячена вивченню традиції спорудження дерев’яних стовпових гробниць Північного Причорномор’я доби бронзи — початку раннього залізного віку. Робиться висновок про її конвергентну появу за доби пізнього бронзового віку у іраномовного населення Євразії. Її розвиток у перед- і ранньоскіфський час в Степу та Лісостепу Північного Причорномор’я відбувався у результаті взаємодії місцевих белозерських та східних (центральноказахстанських) елементів. На цей процес впливали культурні імпульси з Центральної Європи. The article is dedicated to the investigation of the tradition associated with the building of wooden pillar tombs in the North Black Sea region of the Bronze Age — the beginning of the early Iron Age. The results indicated that this tradition resembles the one that appeared among Iranian-speaking population in the late Bronze Age. The development of the tradition on the territory of the steppe and forest-steppe of the North Black Sea region in the pre- and early Scythian times resulted from the interaction of the local Belozersky and eastern (peculiar for central Kazakhstan) elements. The cultural impulses from Central Europe had a particular impact on this process.
Keywords: Північне Причорномор’я; доба бронзи; ранній залізний вік; стовпові гробниці; іраномовні кочовики; the North Black Sea region; the Bronze Age; the early Iron Age; pillar tombs; the Iranian-speaking nomads